Endoscopic Endonasal Transclival Approaches: Case Series and Outcomes for Different Clival Regions - Little, Ryan E.; Taylor, Robert J.; Miller, Justin D.; Ambrose, Emily C.; Germanwala, Anand V.; Sasaki-Adams, Deanna M.; Ewend, Matthew G.; Zanation, Adam M. (Journal of Neurological Surgery Part B: Skull Base, 2014)
Objective Transclival endoscopic endonasal approaches to the skull base are novel with few published cases. We report our institution's experience with this technique and discuss outcomes according to the clival region involved.Design Retrospective case series.Setting Tertiary care academic medical centerParticipants All patients who underwent endoscopic endonasal transclival approaches for skull base lesions from 2008 to 2012.Main Outcome Measures Pathologies encountered, mean intraoperative time, intraoperative complications, gross total resection, intraoperative cerebrospinal fluid (CSF) leak, postoperative CSF leak, postoperative complications, and postoperative clinical course.Results A total of 49 patients underwent 55 endoscopic endonasal transclival approaches. Pathology included 43 benign and 12 malignant lesions. Mean follow-up was 15.4 months. Mean operative time was 167.9 minutes, with one patient experiencing an intraoperative internal carotid artery injury. Of the 15 cases with intraoperative cerebrospinal fluid (CSF) leaks, 1 developed postoperative CSF leak (6.7%). There were six other postoperative complications: four systemic complications, one case of meningitis, and one retropharyngeal abscess. Gross total resection was achieved for all malignancies approached with curative intent.Conclusions This study provides evidence that endoscopic endonasal transclival approaches are a safe and effective strategy for the surgical management of a variety of benign and malignant lesions.Level of Evidence 4.
Keywords: clivus; skull base surgery; endoscopic endonasal approach; CSF leak